Estimation of active surface deformation in the eastern Kachchh region, western India: Application of multi-sensor DInSAR technique. (20th February 2021) - Lakhote, Abhishek; Thakkar, M.G.; Kandregula, Raj Sunil; Jani, Chirag; Kothyari, Girish Ch; Chauhan, Gaurav; Bhandari, Subhash
Abstract: The focus of the present study is to estimate the active surface deformation/displacement affecting the landscape of the eastern Kachchh basin with a particular emphasis on the Wagad, Khadir Island, Bela Island, Chorar Island, and adjoining regions by implementing Differential Interferometry Synthetic Aperture Radar (DInSAR) technique using ENVISAT and SENTINEL-1A radar imagery. To evaluate the deformation pattern using DInSAR, we used ENVISAT-ASAR 2003 to 2005 and 2006 to 2009 data products and SENTINEL-1A data set of 2018–2020. The cumulative displacement of 0.2–0.3 cm for the period of 2003–2005 and 0.19–0.22 cm for the period of 2006–2009 has been observed for the South Wagad Fault region. Similarly, the results acquired from SENTINEL-1A data set revealed a cumulative displacement of 0.16–0.18 cm for the period of 2018–2020. The Island Belt Fault zone shows 0.27 cm displacement, while it is 0.10–0.17 cm for the Gedi Fault zone. The rate of deformation estimated from the present study is well corroborated with the existing results of GPS driven uplift rates. The combined results of DInSAR and GPS indicate that the northern part of the Wagad region is deforming much faster than the south Wagad region. The displacement detected to the east of the epicentral zone of the 2001 Bhuj earthquake indicates the presence of a zone of weaker structures, which may trigger a large magnitude earthquake in the future. Our estimated results of the short-term ground displacement are well corroborated with the existing geological information. This ground displacement is attributed to the tectonic subsidence towards the eastern part of the South Wagad Fault region and within the wide zone of the Island Belt Fault and Gedi Fault zones. The areas with a high amount of displacement have experienced continuous seismicity during the last two decades in the Eastern Kachchh region and might encounter moderate to high seismicity in the near future. The results also provide a better understanding of the active surface deformation pattern taking place in the seismically sensitive eastern Kachchh region.